Low-cost devices to prevent SARS-CoV-2 infection during open and laparoscopic surgery (2020)
Objective To establish the association between adipokine levels and markers of periodontal involvement as risk indicators of early stages of RA (eRA) and the interaction between the presence of markers of periodontal disease with adipokine in eRA individuals. Materials and methods Fifty-one patients with a diagnosis of eRA and 51 healthy controls matched for age and sex were studied. Clinical joint condition, clinical and serological markers of disease activity, serum adipokine levels (leptin, adiponectin, resistin, adipsin, vaspin, and IL-6), periodontal diagnosis, presence of Porphyromonas gingivalis, and related IgG1 and IgG2 antibodies were evaluated. Comparisons were made between eRA and healthy controls for periodontal indicators and adipokines. A subgroup analysis was realized with a non-conditional logistic regression to establish the association between the levels of leptin in individuals with eRA and controls according to the periodontal condition, presence of P. gingivalis, or high titers of IgG antibodies against P. gingivalis. Results The condition of overweight or obesity is associated with the diagnosis of eRA (p = 0.05), and these individuals also have higher levels of leptin (p = 0.001) and vaspin (p = 0.007). Higher frequency of P. gingivalis (p = 0.001) was found in the eRa group. Individuals with eRA with higher IgG2 titers against P. gingivalis had higher levels of leptin (OR: 1.66 (CI 95% 1.01–2.73)); however, individuals with periodontitis or P. gingivalis with eRA were associated with highest levels of leptin (OR: 1.86, CI 95% 1.19–24.3; and OR: 2.04, CI 95% 1.37–3 respectively). Conclusions eRA individuals have high levels of leptin and vaspin. However, the presence of periodontitis and related-periodontal disease markers showed an effect only in leptin levels in eRA individuals. Clinical relevance Emphasizing in personalized medicine, monitoring serum leptin levels and periodontitis markers can improve the early diagnosis of RA.